Examination of a Second Region of the HIV Type 1 Genome Reveals Additional Cases of Superinfection - Piantadosi, Anne (Mary Ann Liebert, Inc., 2008)
HIV-1 superinfection may occur at a rate similar to that of initial infection, raising concerns for HIV-1 vaccine strategies predicated on eliciting immune responses similar to those in natural infection. Because of the high rate of recombination during HIV-1 replication, studies examining only one region of the HIV-1 genome are likely to miss cases of HIV-1 superinfection. We examined HIV-1 gag sequences from 14 high-risk Kenyan women in whom superinfection was not detected in a previous study of env sequences. We detected two additional cases of HIV-1 superinfection: one intersubtype superinfection that occurred between 1046 and 1487 days postinfection (DPI) and one intrasubtype superinfection that occurred between 341 and 440 DPI. Our results suggest that studies that examine only small genome regions may lead to underestimates of the risk of superinfection, highlighting the need for more extensive studies examining multiple regions of the HIV-1 genome.